2014
DOI: 10.1007/s00440-014-0548-x
|View full text |Cite
|
Sign up to set email alerts
|

Mixing time of a kinetically constrained spin model on trees: power law scaling at criticality

Abstract: ABSTRACT. On the rooted k-ary tree we consider a 0-1 kinetically constrained spin model in which the occupancy variable at each node is re-sampled with rate one from the Bernoulli(p) measure iff all its children are empty. For this process the following picture was conjectured to hold. As long as p is below the percolation threshold pc = 1/k the process is ergodic with a finite relaxation time while, for p > pc, the process on the infinite tree is no longer ergodic and the relaxation time on a finite regular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Previous work. Before proving our results we recall the main findings of [23] and [12]. We now formally define the critical density for the OFA-jf model:…”
Section: Cutoff and Concentration For Constrained Models On Treesmentioning
confidence: 89%
“…Previous work. Before proving our results we recall the main findings of [23] and [12]. We now formally define the critical density for the OFA-jf model:…”
Section: Cutoff and Concentration For Constrained Models On Treesmentioning
confidence: 89%
“…Although this bound has been greatly improved for special choices of the update family U , yielding in some cases the correct behavior (cf. [10,13,14]), for general KCM and contrary to the situation of bootstrap percolation in two dimensions, there is yet no universality picture for the scaling of E µ (τ 0 ). The present paper represents the first step of a general project concerning KCM with update family U satisfying q c (U ) = 0, with the aim of establishing universality results on the scaling of E µ (τ 0 ) as q → 0 analogous to those proved within bootstrap percolation.…”
Section: Introductionmentioning
confidence: 93%
“…Constrained Poincaré inequalities for KCM, implying a positive spectral gap and exponential mixing, have already been established [12], mainly using the so-called halving method. Here, inspired by our previous analysis of KCM on trees [10,24], we develop an alternative method which, besides being more natural and direct, applies as well to update families with a large (depending on q) or infinite number of elements. As an example, in section 2.2 we prove a Poincaré inequality for the KCM for which the constraint requires that the oriented neighbours of the to-be-updated vertex belong to an infinite cluster of infected vertices.…”
Section: Introductionmentioning
confidence: 99%
“…Asymptotic Relaxation.-The asymptotic relaxation to zero, φ(t → ∞) → 0, on times t/t σ 1 is governed by a scaling function, φ(t → ∞) = φ(t/t σ ) [61]. For the ofa it has been shown that φ(t) ∝ exp(−t/τ α ) where τ α ∼ σ −γ and the exponent γ ≥ 2 could only be bounded from below [63]. In terms of the scaling function we find τ α ∼ t σ and in particular the preceding analysis determines the exponent γ ≡ γ compatible with the bound.…”
Section: Theorymentioning
confidence: 99%